THE EATING DISORDER EXAMINATION - A SEMISTRUCTURED INTERVIEW FOR THE ASSESSMENT OF THE SPECIFIC PSYCHOPATHOLOGY OF EATING DISORDERS - Cooper, Z; Fairburn, C (1987)
The specific psychopathology of anorexia nervosa and bulimia nervosa is complex in form. Although for many purposes self-report questionnaires are a satisfactory measure of this psychopathology, for detailed psychopathological studies and for investigations into the effects of treatment, more sensitive and flexible assessment measures are required. For this reason a semi-structured interview was developed. This interview, the Eating Disorder Examination, is designed to assess the full range of the specific psychopathology of eating disorders, including these patients' extreme concerns about their shape and weight.